Post corona infection cardiac abnormalities and the risk for sudden cardiac death. (11th May 2021) - Van Hattum, J; Spies, JL; Verwijs, SM; Verwoert, GC; Boekholdt, SM; Groenink, M; Pinto, YM; Wilde, AAM; Jorstad, HT
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): Dutch Olympic Committee*Dutch Sports Federation (NOC*NSF) Amsterdam Movement Sciences (AMS) Most studies investigating the cardiotropic effects of SARS-CoV-2 focus on cardiac complications in severely ill patients. Little is known about eventual sustained cardiac involvement after recovery from COVID-19, especially in patients with a moderate or mild course of illness. Furthermore, as physical exercise can potentially worsen the prognosis of patients with COVID-19 peri- or myocarditis, cardiac involvement in athletes or in the physically active population warrants investigation. Finally, the risk of arrhythmias in such individuals remains largely unknown. We aim to provide a comprehensive overview of myocardial and pericardial involvement after SARS-CoV-2 infection, long-term cardiac sequelae after infection, and risks of SCD/SCD in a predominantly healthy/physical active population, including athletes. We performed a systematic PubMed and MedRxiv search through December 19th, 2020, with the combined terms or synonyms for: COVID-19, SARS-CoV-2, cardiovascular imaging, cardiac MRI, athletes. Exclusion criteria were: no CMR investigations reported, ≥1 comorbidities, age ≤16 years, and reviews. Two investigators independently screened and assessed all identified manuscripts, and additionally searched for reported arrhythmia outcomes. The initial search yielded 127 papers; after extensive review, we included a total of nine papers comprising 607 recovered post-COVID patients/athletes. The table summarises the main CMR findings. No study reported arrhythmias except for Ho et al. who found 18% undefined arrhythmias at baseline. In 5 studies in 201 patients, the weighted mean for the prevalence of elevated T1 was 55%, elevated T2 48%, myocardial LGE 35%, and pericardial LGE 17%. One study (Knight et al.) did not report T1 and T2 measurements. Ho et al. and Ming-Yen et al. found respectively 40% and 19% of patients to meet the Lake Louise Criteria (LLC) for myocarditis; Puntmann et al. reported that 60% had active myocardial inflammation. Second, in 1 study in 139 healthcare workers, the mean for the prevalence of elevated T1 was 42%, T2 4%, LGE 30%, and 5% met LCC for myocarditis. Third, in 3 studies in 96 athletes, the weighted mean for the prevalence of elevated T1 was 21%, T2 24%, myocardial LGE 4%, and pericardial LGE 29%. Brito et al., Clark et al. and Rajpal et al. reported that respectively 0%, 5% and 15% met the LCC for myocarditis. Studies investigating peri- and myocardial sequelae after SARS-CoV-2 infection report varying prevalences of cardiac abnormalities. Such studies are limited in numbers, generally include a low number of individuals, and report no follow-up; only 1 study reported non-specified arrhythmia outcomes. Based on the available studies, the short-term risk for post-COVID-19 SCD due to arrhythmias caused by myocardial inflammation appears to be low. Prospective investigations in larger, well-defined populations, including longer-term follow up and arrhythmia monitoring, are urgently needed.